Perilaku Pembelian Tak Terkendali Pada Healthy Lifestyle Generasi Z: Mengeksplorasi Peran Moderasi Self-Control - Desak Made Febri Purnama Sari; Ni Kadek Dwijayanti Kusuma Putri (Journal Research of Management, 2025)
The rise of healthy lifestyle trends among Generation Z has shifted consumption from health-driven decisions toward identity-based purchasing behavior. This study investigates the influence of Relative Advantage and Compatibility on Impulsive and Compulsive Buying, and further examines the moderating role of Self-Control. A quantitative approach was employed using purposive sampling, involving 220 Gen Z respondents in Bali who actively engage in healthy lifestyle activities. Data were analyzed using PLS-SEM with SmartPLS. The results reveal that Relative Advantage does not significantly affect Impulsive Buying nor Compulsive Buying, indicating that perceived health benefits are not the primary stimulus of consumption. In contrast, Compatibility significantly enhances both types of unrestrained buying, suggesting that alignment between a healthy lifestyle and personal identity drives consumers to engage in spontaneous and repeated purchases. The moderating effect of Self-Control was not supported, implying that internal regulation is insufficient when social norms strongly encourage a healthy lifestyle as a status symbol. Additionally, Impulsive Buying positively predicts Compulsive Buying, demonstrating the escalation from spontaneous to addictive consumption patterns. This study extends the S-O-R and Diffusion of Innovation frameworks by highlighting that healthy lifestyle adoption among Gen Z is primarily socially driven rather than functionally motivated. Practical implications recommend more ethical marketing strategies within the wellness industry, emphasizing mindful consumption and financial well-being